Transient elastography is useful in diagnosing biliary atresia and predicting prognosis after hepatoportoenterostomy - Wu, Jia‐Feng; Lee, Chee‐Seng; Lin, Wen‐Hsi; Jeng, Yung‐Ming; Chen, Huey‐Ling; Ni, Yen‐Hsuan; Hsu, Hong‐Yuan; Chang, Mei‐Hwei (Hepatology (Baltimore, Md.), 2018)
We investigated the utility of transient elastography (TE) for diagnosing biliary atresia (BA) in cholestatic infants and predicting the outcome of BA. Forty‐eight cholestatic infants (9‐87 days of age) with direct bilirubin level >1 mg/dL were enrolled. Liver stiffness measurement (LSM) by TE was performed during the cholestasis workup, and 15 subjects were diagnosed as BA. We assessed liver histology using liver biopsies from 36 subjects and graded fibrosis status using the METAVIR score. BA infants had significantly higher LSM values and METAVIR scores than non‐BA cholestatic infants. A receiver operating characteristic (ROC) curve analysis showed that an LSM >7.7 kPa was predictive of BA among cholestatic infants (sensitivity = 80%; specificity = 97%; area under the curve [AUC] = 85.3%; P = 0.0001). Cholestatic infants with an LSM >7.7 kPa were more likely to be diagnosed with BA (odds ratio [OR] = 128; P < 0.001). Very early measurement of LSM after hepatoportoenterostomy (HPE) is associated with occurrence of thrombocytopenia, splenomegaly, and esophageal varices 6 months post‐HPE. Five of the BA subjects were awaiting or had received liver transplantation (LT), and they had a significantly higher LSM measured 1 week post‐HPE than that in the other BA subjects (26.0 vs. 10.8 kPa; P = 0.006). A Cox proportional analysis demonstrated that the need for LT was significantly higher in BA subjects with LSM >16 kPa measured 1 week post‐HPE than other BA subjects (hazard ratio [HR] = 10.16; P = 0.04). Conclusion: LSM assessment during the workup of cholestatic infants may facilitate the diagnosis of BA. LSM post‐HPE may predict complications and the need for early LT in infants with BA. (Hepatology 2018).